Depiction of an episode from Jinachandra Suri's life - Temples of India Project Team (Jio Institute, 2024)
The third oval painting (in clockwise order) in the lower/outer circle in the ceiling of the mandapa (pillared hall) depicts an episode from Jinachandra Suri's life. Once, a disciple of Jinachandra Suri mistakenly told a Muslim religious leader it was a no-moon day when it was a new moon day. The Muslim leader spread the misinformation across the city, questioning the disciple’s knowledge of the day. To rectify the situation, Jinachandra Suri threw a gold plate into the sky, covering the moon and thus converting the day into a no-moon day. This miracle is supposed to have taken place in front of Emperor Akbar. The inscription reads, ‘Shri Jinachandra Suri ji na Purnima kari.’